Bst polymerase — a humble relative of Taq polymerase - Igor Oscorbin; Maxim Filipenko (Computational and Structural Biotechnology Journal, 2023)
DNA polymerases are a superfamily of enzymes synthesizing DNA using DNA as a template. They are essential for nucleic acid metabolism and for DNA replication and repair. Modern biotechnology and molecular diagnostics rely heavily on DNA polymerases in analyzing nucleic acids. Among a variety of discovered DNA polymerases, Bst polymerase, a large fragment of DNA polymerase I from Geobacillus stearothermophilus, is one of the most commonly used but is not as well studied as Taq polymerase. The ability of Bst polymerase to displace an upstream DNA strand during synthesis, coupled with its moderate thermal stability, has provided the basis for several isothermal DNA amplification methods, including LAMP, WGA, RCA, and many others. Bst polymerase is one of the key components defining the robustness and analytical characteristics of diagnostic test systems based on isothermal amplification. Here, we present an overview of the biochemical and structural features of Bst polymerase and provide information on its mutated analogs.